2014
DOI: 10.1159/000377624
|View full text |Cite
|
Sign up to set email alerts
|

Peritoneal Submesothelial Stromal Cells Support Hematopoiesis and Differentiate into Osteogenic and Adipogenic Cell Lineages

Abstract: The peritoneum is a thin membrane that covers most of the abdominal organs, composed of a monolayer of mesothelial cells and subjacent submesothelial loose connective tissue. Cells from the peritoneal wall are correlated with peritoneal fibrosis and epithelial-to-mesenchymal transition. However, the distinct involvement of mesothelial or submesothelial cells in such phenomena is still not clear. Here, we propose a new strategy to obtain stromal cells from anterior peritoneal wall explant cultures. These cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 40 publications
(44 reference statements)
0
6
0
Order By: Relevance
“…MC expresses additional biochemical markers suggesting an active role of these cells in fluid transport, initiation and resolution of inflammation. These biochemical markers include aquaporin 1, sodium-potassium adenosine triphosphatase (Na + /K + -ATPase), sodium bicarbonate cotransporter (SLC) [20], integrin β1 (CD29) [26][27][28], CD40 as a member of the tumor necrosis factor (TNF)-receptor…”
Section: Phenotypic or Biochemical Markers Of MCmentioning
confidence: 99%
“…MC expresses additional biochemical markers suggesting an active role of these cells in fluid transport, initiation and resolution of inflammation. These biochemical markers include aquaporin 1, sodium-potassium adenosine triphosphatase (Na + /K + -ATPase), sodium bicarbonate cotransporter (SLC) [20], integrin β1 (CD29) [26][27][28], CD40 as a member of the tumor necrosis factor (TNF)-receptor…”
Section: Phenotypic or Biochemical Markers Of MCmentioning
confidence: 99%
“…Mesothelial cells have also been isolated from adherent or free-floating ascites, lavage, and exudate sources and often also cultured; as such, these cells as well as subserosal cells have been shown to possess multiple properties [ 143 , 144 , 145 ]. However, it is not clear whether free-floating cells are the same as adherent cells, if contaminated mesothelial cell populations have been isolated due to lack of additional purification steps or whether selection pressures during culture have influenced the cell population analysed and/or its phenotype.…”
Section: Further Discussion and Areas Of Future Researchmentioning
confidence: 99%
“…The submesothelial reactive response to tissue damages has been described in distinct models 31–33 . Recently, our group demonstrated that submesothelial cells derived from peritoneal explants have fibroblast-like behavior, mesenchymal phenotype, and stromal functions 34,35 . The pristane-model was marked by important disturbances on oil granuloma formation in Lgals3 −/− mice, including large necrotic areas and high levels of IL-6 7 .…”
Section: Discussionmentioning
confidence: 99%